DEVELOPMENT OF VALUE ENRICHED YOGHURT WITH SOY MILK AND MUSA PARADISIACA PULP - V. Jayalalitha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An attempt has been made to develop value added yoghurt with soymilk by replacing cow milk with incorporation of 10,20 and 30% levels of soy milk. On physicochemical and sensory quality test 30 % level of soy milk incorporation found to be acceptable. Further another study carried out to enrich yoghurt by addition of banana pulp at the rate of 5,10 and 15% levels. The 15% banana pulp enriched soy yoghurt found to be acceptable. Further the protein and total solids content is significantly differ from the control yoghurt. An increase in lactose and total solids content has been observed in banana pulp enriched product than control.